Networks and norm entrepreneurship amongst local civil society actors: advancing refugee protection in the Asia Pacific region. Issue 2 (17th February 2016) - Nah, Alice M.
Abstract : Research on transnational advocacy networks has tended to focus on how non-state actors from developed countries interact with those from developing countries to pressure states, often by drawing in liberal Western states. This article adds a different perspective, focusing on how local civil society actors in different locales interact with each other to persuade their own governments 'from below'. It examines how these actors facilitate norm emergence amongst Asian states on issues with little domestic traction and for which there are well-developed international norms, standards and procedures. In studying the way local civil society actors conduct norm entrepreneurship, it is important to recognise the political, material and ideational conditions that constrain their work; their positionality and fragility in their own societies; and the way they relate to other actors working on the same issues. Focusing on the case of the Asia Pacific Refugee Rights Network, it is argued that working through a formalised network has changed the ways and the conditions under which local civil society actors engage in norm entrepreneurship on refugee protection. It has changed the attributes of actors, helping them develop visibility, capacity and connectedness through the formation of a 'community of practice'; it has changed power relations between them and other actors – in particular, the United Nations High Commissioner for Refugees; it has facilitated the development of 'regional imagination' and the practice of 'scale shifting', helping local actors move beyond domestic contexts to engage with state and non-state actors through regional and international fora. It has also introduced shifts in the dynamics of norm entrepreneurship by introducing a new actor – the network itself, which exercises agency through a Secretariat – and intra-network sensitivities, which need careful attention to prevent member disengagement.